Penurunan Nilai Glukosa Darah Sewaktu (GDS) Pada Pemain Badminton Di Kota Makassar - Siti Rahmani; Sri Wahyuni; Alfyan Rahim; Ajay Qumar Sagala (NHM PRESS, 2023)
Fatigue is one of the events that triggers injury to badminton players/athletes when playing or after playing, so that by doing physical activity (exercise) can improve fitness and reduce and maintain blood glucose levels to stay within the normal range through the energy used when playing / exercising. Knowing the right carbohydrate (energy) needs and the condition of blood glucose levels can prevent excessive fatigue when playing and after playing. To determine changes in blood glucose values ​​during (GDS) on badminton players in Makassar City.The research method used was quasi-experimental using the One Group Pretest-Posttest design. This research was conducted on 6-15 February 2023 at a sports hall (GOR) in Makassar consisting of 22 respondents in the intervention group (playing badminton) using single mode (1vs1) 2 sets system (per 21 points). It can be concluded that there is a change in the form of a decrease in blood glucose values ​​(GDS) for badminton players in the city of Makassar, an average decrease of 12 mg/dl. The suggestion from this study is that it is proven that by playing badminton using single mode (1vs1) a 2-set system (per 21 points) there can be a change in the GDS value for badminton players on average decreasing by 12 mg/dl. So this can be a way for those who want to lower blood glucose levels.